COMPLEX ANALYSIS OF DENTAL STATUS IN CHILDREN WITH ALLERGIC DISEASES - R.S. Nazarian; L.S. Kryvenko (Український стоматологічний альманах)
The article presents data on the complex analysis of the dental status of 126 children with asthma, allergic rhinitis and atopic dermatitis. Allergic diseases are an important problem of modern medicine because sensitization of adult and child population is growing. In Ukraine, the frequency of allergic diseases has been increased in 1.5 times for the last 5 years.